The Influence of Brand Image and Financial Technology on Customer Loyalty - Ependi, Ependi (ProBisnis : Jurnal Manajemen, 2023)
This research aims to determine the influence of Financial Technology's brand image on PT Kredit Pintar's customer loyalty. The method used in this research is a descriptive analysis method with a quantitative approach. The sample used in this research was 62 respondents using a questionnaire. The collected data was processed using multiple linear regression with SPSS 26.00. The research results show that Brand Image has a significant effect, Financial Technology has a significant effect on customer loyalty, and brand image and financial technology have a simultaneous effect on customer loyalty. This research concludes that there is a positive and significant influence on customer loyalty between brand image and financial technology. Suggestions for future researchers are that the research covers a broader scope, such as adding other variables.